1973
DOI: 10.1021/jf60190a036
|View full text |Cite
|
Sign up to set email alerts
|

Gel chromatography of sunflower proteins

Abstract: a company or product name by the department does not imply approval or recommendation of the product to the exclusion of others which may also be suitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 11 publications
5
33
0
Order By: Relevance
“…Several authors have claimed that, in sunflower products, CGA appears mainly in the form of complexes or bound to proteins. The binding to sunflower proteins has been reported to occur either preferentially with low‐molecular‐weight proteins48–52 or high‐molecular‐weight proteins53 or non‐preferentially 54, 55. Non‐covalent interactions of both caffeic and quinic acids (constituents of CGA) with helianthinin have also been reported 56.…”
Section: Phenolic Compounds Of Sunflower Seedmentioning
confidence: 99%
“…Several authors have claimed that, in sunflower products, CGA appears mainly in the form of complexes or bound to proteins. The binding to sunflower proteins has been reported to occur either preferentially with low‐molecular‐weight proteins48–52 or high‐molecular‐weight proteins53 or non‐preferentially 54, 55. Non‐covalent interactions of both caffeic and quinic acids (constituents of CGA) with helianthinin have also been reported 56.…”
Section: Phenolic Compounds Of Sunflower Seedmentioning
confidence: 99%
“…The major storage proteins in bean seeds are summarized as follows: (1) albumins (2S fraction; 20% to 30% of total proteins, soluble in water) consisting of two dimers (PA1, 11 kDa and PA2, 25 kDa) and tetramer (lectin, 50 kDa) and (2) globulins (50% to 75% of total proteins, soluble in salt) containing vicilin (7S fraction; a 50-kDa trimer), legumin (11S fraction; α acid and ß basic polypeptides of 40 and 20 kDa, respectively, bound by a disulfide bridge), and convicilin (a 71-kDa trimer) [24,25]. In the present investigation, we examine the impact of copper excess on bean seed germination, embryonic growth, and changes in the cotyledonary biomass mobilization, particularly, the breakdown of albumin and globulin.…”
Section: Introductionmentioning
confidence: 99%
“…Rahma and Rao (1979) observed that while there are many reports on the processing and technological aspects of sunflower oil and meal, data on characterization of proteins are meager. This was also confirmed by Sabir et al, 1973;Baudet and Mosse, 1977). Rahma and Rao conducted a study to determine the characterization of the proteins of sunflower cultivated in India.…”
Section: Sulfur 1943mentioning
confidence: 71%